How Missile Engineering is Taking Product Line Engineering to the Extreme at Raytheon. Issue 1 (20th September 2021) - Young, Bobbi; Sanderson, Tom; Thurman, Matt; Turpin, Jeffrey; O'Keefe, Elizabeth; Clements, Paul
Abstract: This paper describes a new approach to designing and building missiles by Raytheon Missile and Defense Systems. Key aspects of the approach include (1) modular common components connected through identified standards, (2) modular open systems approaches and standards based interfaces, (3) Feature‐based Product Line Engineering (FbPLE) practices for identifying commonality and managing variation, and (4) implementing digital transformation through digital engineering capabilities to begin a missile's digital twin. Much more ambitious than simply reusing existing component designs from previously built missiles, this approach involves automatic generation, exploration, and pruning of an automatically generated trade space of possible missile designs that satisfy a given set of requirements. The goal is to radically lower development and production costs by rapidly settling on a viable design that can be taken to design validation, then complete design and production, all in a digital ecosystem. The paper focuses on the FbPLE aspect of the engineering approach and shows how its technology is used to create and manage the trade space, and then create a digital twin of a chosen design.